Marketing Strategies Applied by LSP Ditekindo to Increase Sales - Astuti, Aurelia Widya; Rosidah, Rosidah (Al-Makki Publisher, 2025)
In the era of rapid globalization, the Professional Certification Agency (LSP) Ditekindo is faced with significant challenges to increase sales of its certification services. Intense competition with other certification bodies requires LSP Ditekindo to adopt effective and innovative marketing strategies. This study aims to describe the marketing strategy implemented by LSP Ditekindo and evaluate its effectiveness in the face of changing market dynamics. The approach used is qualitative with data sources from in-depth interviews and observations at LSP Ditekindo. Data analysis was conducted using the methods of reduction, presentation, and conclusion drawing. LSP Ditekindo successfully implemented a marketing strategy that includes increased branding on social media, strategic partnerships with educational institutions, and analysis of customer needs and preferences. The implementation of this strategy showed an increase in sales volume and brand awareness. The implementation of effective marketing strategies has proven to increase LSP Ditekindo's competitiveness in the professional certification market. Customer feedback and market analysis are continuously conducted to improve and adjust the existing strategies. LSP Ditekindo has successfully increased sales and brand image through relevant marketing strategies. Future research is recommended to use a quantitative approach to measure the impact of each marketing strategy element.